Afrontamiento del trastorno de déficit de atención e hiperactividad por parte de los docentes de educación básica primaria del colegio Lancaster de la ciudad de Cali (2023)
Attention-deficit/hyperactivity disorder (ADHD) is characterized, according to the DSM-V (2013), by symptoms such as: hyperactivity, impulsivity and inattention or difficulty concentrating on a topic or object. For this reason, children who have this disorder usually manifest it mainly in the school environment, and that is where the teaching staff has a fundamental role. Based on the above, the objective of this study was to identify the knowledge about ADHD that the teachers of the first grade of Primary Education at the Lancaster bilingual school had, in the same way, to characterize and evaluate the coping strategies applied by the teachers in the educational institution in particular cases of ADHD.